Experience of the Lutein drugs use for the treatment of dysmenorrhea - N. V. Avramenko; I. B. Gridina; E. A. Lomeyko; I. V. Semenenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Treatment of dysmenorrhea is a very important question. Dysmenorrhea is a cyclic pathological process, manifested by pain in the lower abdomen in the days of menstruation and is accompanied by emotional-mental, vegetative, vegetative-vascular and metabolic endocrine symptoms. Dysmenorrhea is divided into primary, in which you cannot identify pathological changes in the genital organs, and secondary, associated with gynecological diseases (most often inflammatory diseases of the genital organs and endometriosis).